Familial aggregation of juvenile idiopathic arthritis with other autoimmune diseases: Impact on clinical characteristics, disease activity status and disease damage. (29th June 2021) - Al‐Mayouf, Sulaiman M.; Alrasheedi, Abeer; Almsellati, Iman; Hashad, Soad; Khawaja, Khulood; Abdwani, Reem; AlHashim, Samia; Muzaffer, Mohammed; Lotfy, Hala; Almutairi, Nora
Abstract: Objectives: To evaluate the impact of family history of autoimmune diseases (FHADs) on the clinical characteristics and outcome of juvenile idiopathic arthritis (JIA). Methods: We retrospectively reviewed children with JIA seen in 7 pediatric rheumatology clinics from 6 Arab countries. All included patients met the International League of Associations for Rheumatology classification criteria for JIA and had a disease duration greater than 1 year. Data were collected at the last follow‐up visit and comprised clinical findings, including FHADs. Disease activity and disease damage were assessed by Juvenile Arthritis Multidimensional Assessment Report, and juvenile arthritis damage index (JADI) respectively. Disease activity was categorized as remission off treatment, remission on treatment, or active disease. Results: A total of 349 (224 females) JIA patients with a disease duration of 5 (interquartile range 2.9‐7.5) years were included. The most frequent JIA categories were polyarticular JIA and oligoarticular JIA, followed by systemic JIA. There were 189 patients with FHADs and 160 patients without FHADs. The most frequent FHADs were diabetes mellitus (21.2%), JIA (18.5%), rheumatoid arthritis (12.7%). Among patients with FHADs, 140/189 (74.1%) achieved clinical remission, while 131/160 (81.9%) patients without FHDs had clinical remission (odds ratio [OR] = 1.2, 95% CI 0.97‐1.5). Rate of consanguinity, enthesitis‐related arthritis (ERA) and psoriatic arthritis were higher in patients with FHADs (OR = 0.6, 95% CI 0.4‐0.9 and OR = 1.2, 95% CI 1.1‐1.4). Also, articular JADI correlated significantly with presence of FHADs (OR = 1.1, 95% CI 1.0‐1.1). Conclusion: This study shows that autoimmune diseases cluster within families of patients with JIA with a high proportion of ERA and psoriatic arthritis. JIA patients with FHADs are likely to have more disease damage.